EVALUATION OF INCIDENCE OF DISPLACEMENT OF PPIUCD INSERTED AFTER VAGINAL AND CAESAREAN DELIVERY IN TERTIARY CARE CENTRE: A COMPARATIVE STUDY - Nagaria, Tripti; Sapaha, Deepti; Khan, Anjum (International Journal of Pharma and Bio Sciences, 2026)
Postpartum intra-uterine contraceptive devices (PPIUCD) are IUCDs that are inserted immediately following the delivery of the placenta or up to 48 hours after birth. The most common complications of PPIUCD are heavy vaginal bleeding, menstrual irregularities, abdominal discomfort, fever, unusual vaginal discharge, missing strings, expulsion, displacement, and rarely perforation. Therefore, the present study was conducted for a comparative evaluation of the incidence of displacement and other complications of PPIUCD inserted after vaginal and cesarean delivery in cases delivered at tertiary care hospitals.: The study was designed as an observational study conducted at the Department of Obstetrics and Gynecology in Pt. J.N.M. Medical College and Dr. BRAM Hospital in Raipur, Chhattisgarh. The study spanned from August 2022 to December 2023. The study population was antenatal clients who came to Antenatal OPD or those who got admitted to the labor room to undergo vaginal or cesarean delivery and given consent for PPIUCD insertion. The statistical software SPSS 22.0 was used to analyze the data. The total number of PPIUCD insertions was 5475 (43%). Out of which 2471 (45%), PPIUCD insertions were done after vaginal delivery, and 3004 (55%) were intra-caesarean insertions. PPIUCD was more invaginal PPIUCD group (12%) than caesarean PPIUCD group (3.9%). The present study concludes that PPIUCD is an effective, safe, and convenient intervention both in vaginal and caesarean deliveries.